2017
DOI: 10.1021/acs.biomac.7b00760
|View full text |Cite
|
Sign up to set email alerts
|

Sustained Release of a Peptide-Based Matrix Metalloproteinase-2 Inhibitor to Attenuate Adverse Cardiac Remodeling and Improve Cardiac Function Following Myocardial Infarction

Abstract: Following myocardial infarction (MI), degradation of extracellular matrix (ECM) by upregulated matrix metalloproteinases (MMPs) especially MMP-2 decreases tissue mechanical properties, leading to cardiac function deterioration. Attenuation of cardiac ECM degradation at the early stage of MI has the potential to preserve tissue mechanical properties, resulting in cardiac function increase. Yet the strategy for efficiently preventing cardiac ECM degradation remains to be established. Current preclinical approach… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
56
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 78 publications
(58 citation statements)
references
References 54 publications
(157 reference statements)
2
56
0
Order By: Relevance
“…Upon injection of the 10% hydrogels into a MI rat model, they found that, at 10 weeks postinjection, pathogenic ventricular remodeling was attenuated in these rats (compared to controls). In another experiment, Fan et al demonstrated that a thermosensitive PNIPAAm– co –HEMA– co –AOLA hydrogel loaded with a MMP‐2 inhibitor displayed a stiffness of 35 kPa when produced using a high concentration of PNIPAAm– co –HEMA– co –AOLA (20% w/v). This relatively stiff system efficiently prevented cardiac ECM degradation in a MI rat model and improved cardiac function.…”
Section: Design Of Injectable Hydrogels For Cardiac Tissue Engineeringmentioning
confidence: 99%
“…Upon injection of the 10% hydrogels into a MI rat model, they found that, at 10 weeks postinjection, pathogenic ventricular remodeling was attenuated in these rats (compared to controls). In another experiment, Fan et al demonstrated that a thermosensitive PNIPAAm– co –HEMA– co –AOLA hydrogel loaded with a MMP‐2 inhibitor displayed a stiffness of 35 kPa when produced using a high concentration of PNIPAAm– co –HEMA– co –AOLA (20% w/v). This relatively stiff system efficiently prevented cardiac ECM degradation in a MI rat model and improved cardiac function.…”
Section: Design Of Injectable Hydrogels For Cardiac Tissue Engineeringmentioning
confidence: 99%
“…This is especially true for heart injection as the beating heart muscle squeezes out the injected delivery medium. Quick increase of viscosity of the delivery medium upon injection by fast gelation represents one of the strategies to increase cell retention [47, 51, 68]. Figure 8B demonstrates that the developed hydrogel significantly increased MSC retention in the muscles compared to slow gelling collagen, and non-gelling PBS.…”
Section: Discussionmentioning
confidence: 99%
“…However, the hydrogels will be injected into the infarcted region where electrical conductivity is very low. In addition, it is unclear how much disruption of electrical conductivity will cause heart tissue arrhythmias [47, 51, 68]. Previous studies using hydrogels with relatively fast gelation rate did not experience obvious arrhythmias.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations